169Folic acid intake and dementia - a 27-year global longitudinal study. (2nd September 2021) - Suzuki, Norie; Shirai, Yoshiro; Abe, Chisato; Imai, Tomoko; Sezaki, Ayako; Miyamoto, Keiko; Kawase, Fumiya; Inden, Ayaka; Kato, Takumi; Sanada, Masayo; Shimokata, Hiroshi
Abstract: Background: Folate deficiency increases serum homocysteine and may cause cognitive impairment. However, there have been no international longitudinal studies that examined the association between folic acid intake and dementia. We investigated the longitudinal association between folate intake and the prevalence of dementia using global data during 27 years. Methods: Prevalence of Alzheimer's disease and other dementias and folic acid intake by country were obtained from the Global Burden of Disease (GBD) 2017 database. The longitudinal associations between folic acid intake and prevalence of dementia was examined using linear mixed effect model during 27 years from 1990 to 2017 in 151countries with populations of 1 million or greater. The effects of folic acid, year and interaction of folic acid and year were estimated controlling for covariates including socio-economic variables and life-style variables. Results: Fixed effects of folic acid was highly significant (mean and SE; -33.1±7.1, p < 0.001) and interaction of folic acid and survey year was also significant (0.90±0.13, p < 0.001). Slope of folic acid for dementia prevalence was significant in 1990 and the slope has decreased with the year and has become not significant after 2011. Conclusions: Folic acid was associated with the prevalence of dementia, but weakened over the years. Key messages: Although folic acid intake has been associated with the of dementia, the risk of dementia may be increasingly related to factors other than nutrition.